A century of happiness in children’s literature (1920–2020): A Stalinist canon and its long term consequences - K. A. Maslinsky (Шаги)
In the Stalin era, the category of happiness was sharply politicized, and a new canon of representation of Soviet happiness was established in literature and cinema. The article presents empirical data that permits a quantitative evaluation of the scale and nature of the Stalinist transformation of the happiness narrative in a single genre — realistic children’s prose. The corpus of 19th–20th century Russian prose for children and youth (Detcorpus) served as the source of data. The scale of changes was assessed by measuring the frequency of the lexemes ‘happiness’ and ‘happy’ in the corpus. Semantic transformations were assessed based on changes in the contexts of the use of these lexemes, measured using diachronic word embeddings. The results of the study partially confirm the findings of previous studies and raise new questions. In particular, the number of mentions of happiness dropped sharply in children’s literature in the 1920s. It can be assumed that the “cancellation” of happiness was the first stage in the formation of the Stalinist canon. The data also provides evidence that, starting in the Stalin period, emotions became much more relevant in the representation of happiness in children’s literature. This process could also be linked to the formation of the Stalinist canon.